PENERAPAN E-GOVERNMENT DALAM PROGRAM DUMAI BERKHIDMAT OLEH PEMERINTAH KOTA DUMAI TAHUN 2023 - Nadhif, Reyhan Ivan; Susanto, Agus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The use of digital technology in public organizations is currently unavoidable. Advances in information technology provide the greatest benefits for the benefit of society. Road infrastructure is an absolute necessity in the road transport system to support economic, social, cultural, as well as defense and security activities. This research intends to find out implementation e-Government in the Dumai Berkhidmat Program by the Government of Dumai City in 2023 in complaints and reports from the community about the damaged roads in Dumai City in the field of infrastructure services of the Dumai Berkhidmat application. Research Location in Dumai City. This research uses the theory according to Rianto and Tri Lestari, namely general complaints and poverty complaints, Software, Hardware, Data and Information, Human Resources (HR) and Implementing Attitudes, Communication, and Organizational Structure. The results of this research show that with the presence of the Dumai Berkhidmat application through the Infrastructure Service sector, the Dumai City Government through the Public Works and Public Housing Department is always consistent with reports and complaints from the public regarding damaged roads in Dumai City. And by always maintaining intense communication between the Government (OPD) and the community, it shows that their presence as one of the supports for this application-based service encourages the community to be able to report any problems that exist in Dumai City and evaluate the performance of the apparatus. Keywords: Application, Road Broken, Report, Government, E-government